Halide perovskite-based mechanical energy harvester for self-powered sensing - Jiang, Feng (Nanyang Technological University, 2025)
The rapid advancement of wearable electronics has intensified the demand for efficient power supply and intelligent sensing systems. Mechanical energy harvesters, such as triboelectric nanogenerators (TENGs) and tribovoltaic nanogenerators (TVNGs), offer effective means by converting mechanical energy from the environment and human movements into electricity. This provides a sustainable and self-powered solution for driving multifunctional electronic devices and sensing systems. Among various materials, halide perovskites show their exceptional electrical performance, owing to their tunable energy levels and remarkable ferroelectricity. However, the comprehensive understanding of halide perovskite interfaces, including charge transfer behaviors and interfacial bonding interactions, remains elusive. This gap necessitates deeper investigation to establish theoretical frameworks and propose potential optimization strategies for fabricating high-performance energy harvesters and sensors. Furthermore, the usage of lead and the moisture sensitivity of halide perovskites make them suffer from high toxicity and poor stability, impeding their further practical applications.